216 – 27q3
⟹ (6)3 – (3q)3
Using the formula (a3 + b3) = (a – b) (a2 + ab + b2)
Here a = 6 and b = 3q.
⟹ (6 – 3q) (36 – 18q + 9q2)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :